Malignant transformation in mature cystic teratoma of the ovary: a case report - Ferdousi, Shamima; Banu, Sultana Gulshana (Bangladesh Journal of Pathology, 2011)
Keywords: ovary-mature cystic; teratoma; malignant transformation DOI: http://dx.doi.org/10.3329/bjpath.v26i1.9150 BJPATH 2011; 26(1): 36-38